An Investigation into Linguistic Features of Antithesis in Political Speeches in English and Vietnamese - Lê Thị Hoàng Vân (2008)
Political speeches in English and Vietnamese are a ‘fertile land’ where this study can investigate and discover the basic characteristics of argumentation power of antithesis and stylistic features of rhetorical devices in antithesis. Based …